Production of Rhamnosyl Icariside II by snailase hydrolysis of Epimedium wushanense extracts - Wang Chen; Gege Liu; Yue Zhang (Heliyon, 2024)
Rhamnosyl Icariside II is a rare secondary flavonoid glycoside isolated from Epimedium L. plants. It has better stability and physiological activity than the primary flavonoid glycosides of Epimedium L., therefore, conversion of the primary flavonoid glycoside into Rhamnosyl Icariside II would be desirable. In this study, a method for the enzymatic production of Rhamnosyl Icariside II from the total flavonoids of Epimedium wushanense was established, and the conditions were optimized. Six commercial enzymes were screened, and the reaction conditions for the best enzyme were optimized. Snailase was the most effective hydrolase, and the highest yield was obtained under the optimized conditions. To facilitate industrial production of Rhamnosyl Icariside II, a scaled-up pilot test was performed. The reaction solution was extracted with n-butanol to obtain the Rhamnosyl Icariside II crude product, which was then subjected to silica gel column chromatography and preparative chromatography. Finally, a product of Rhamnosyl Icariside II with purity of 99.1 % was achieved, in a total yield of 46.8 %. Compared to direct extraction and acid hydrolysis, this method improves the product yield and purity, which is of great significance for the large-scale production of Rhamnosyl Icariside II. This study provides a basis for the physiological activity study of Rhamnosyl Icariside II, and offers possibilities for future applications in the healthcare sector.